A heat-resistant aluminum alloy and a preparation method and application thereof
Patent Information
- Application Number
- CN202311864901.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-29
AI Technical Summary
[0003]传统的加工技术手段主要通过细化晶粒、添加第二相或增加位错来提高材料强度,目前报道的耐热铝合金是基于析出强化机制,其强化效果来自于热处理后形成的L12结构的弥散强化相,但由于晶粒尺度效应的限制,强化效果不明显
[0016]在上述实施过程中,选用激光或电子束作为能量源,扫描合金粉末通过快速熔化、凝固从而达到冶金结合的效果,最终获得模型所设计的组织致密且力学性能良好的金属零件,工艺窗口宽;集材料的凝固过程和加工成形过程于一体,冷却速度快,无需热处理步骤,大大缩短了加工周期,提高了生产效率,简化了工艺流程。同时避免了复杂薄壁结构和变截面结构在热处理过程中变形、翘曲问题,实现了材料加工的结构复杂化、个性化定制和轻量化。且其得到的耐热铝合金具有高强度、高韧性、高耐热性和密度低的特点,能满足不同工况的使用要求,解决了现有耐热铝合金强度不高,高温稳定性差的问题。
Smart Images

Figure CN117778836B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of aluminum alloy materials technology, and more specifically, to a heat-resistant aluminum alloy, its preparation method, and its application. Background Technology
[0002] Heat-resistant aluminum alloys possess advantages such as high specific strength, low density, and good oxidation resistance, leading to their widespread application in industries such as aerospace, automotive, shipbuilding, and weaponry. However, the high-temperature performance of current heat-resistant aluminum alloys is nearing its limit; their mechanical properties significantly decrease above 200℃, making it difficult to meet operating temperature requirements and posing significant safety hazards. Therefore, developing novel heat-resistant aluminum alloys with excellent room-temperature performance, good oxidation and fatigue resistance, and good heat resistance and high-temperature stability is of great significance for aerospace and weight-sensitive applications.
[0003] Traditional processing techniques primarily improve material strength by refining grains, adding a second phase, or increasing dislocations. Currently reported heat-resistant aluminum alloys utilize precipitation strengthening mechanisms, with the strengthening effect derived from the dispersed strengthening phase of the L12 structure formed after heat treatment. However, due to limitations imposed by grain size effects, the strengthening effect is not significant. Al-Si alloys have low mechanical properties, and the addition of Sc and Zr significantly increases costs, hindering widespread application. Aluminum-based composites possess excellent properties such as high strength and high modulus, but their density is low, the reinforcing phase is unevenly dispersed, and defects often exist at the interface between the reinforcing phase and the aluminum matrix, leading to microcracks and failure during use. Al-Zn high-strength aluminum alloys are prone to hot cracking during solidification. While subsequent deformation and heat treatment can improve material strength, as the operating temperature increases, the grains gradually grow and coarsen, causing a sharp decrease in material strength. Moreover, these methods involve long processing cycles, high energy consumption, and complex processes. Summary of the Invention
[0004] The purpose of this application is to provide a heat-resistant aluminum alloy, its preparation method and application, which improves the stability of the heat-resistant aluminum alloy at high temperatures.
[0005] In a first aspect, embodiments of this application provide a heat-resistant aluminum alloy, the chemical composition of which, by mass fraction, includes: Cu: 3.50%–4.50%, Ni: 1.00%–2.00%, Mg: 0.01%–0.75%, Si: 0.5%–1.5%, Zr: 0.01%–0.05%, Er: 0.01%–0.02%, Sr: 0.01%–0.03%, with the remainder being Al and unavoidable impurities; the microstructure of the heat-resistant aluminum alloy includes a primary eutectic phase, a secondary eutectic phase, a Si phase, and a Mg2Si phase, the primary eutectic phase having a three-dimensional network framework structure, the primary eutectic phase including Al2Cu phase and Al2CuMg phase, the secondary eutectic phase, Si phase, and Mg2Si phase distributed within the primary eutectic phase, the secondary eutectic phase including Al3Ni phase, and the Mg2Si phase being granular.
[0006] In the above implementation process, by controlling the chemical composition, a three-dimensional network framework microstructure with nanoscale eutectic Al2Cu and Al2CuMg phases is formed. The uniform distribution of the Al2Cu and Al2CuMg phase network structure enhances the aluminum matrix. Its nanoscale network framework can effectively hinder dislocation movement and microcrack propagation, breaking the scale effect of traditional solidification structures and resulting in a significant strengthening effect. The Al3Ni phase is a secondary eutectic phase with good high-temperature stability, remaining stable even at 400℃, and can coat and inhibit the deformation of the aluminum matrix. The Si phase is a tertiary eutectic phase. The fine and stable eutectic Si phase is distributed in the matrix, which can effectively increase the material's hardness, tensile strength, wear resistance, and corrosion resistance. The three phases mutually depend on each other to nucleate and form a fine mixed eutectic structure, providing casting performance and plasticity; at the same time, the granular Mg2Si phase in the structure produces a strengthening effect.
[0007] As an optional implementation, the chemical composition of the heat-resistant aluminum alloy, by mass fraction, includes: Cu: 3.75%–4.25%, Ni: 1.25%–1.75%, Mg: 0.2%–0.5%, Si: 0.75%–1.25%, Zr: 0.02%–0.04%, Er: 0.0125%–0.0175%, Sr: 0.015%–0.025%, with the remainder being Al and unavoidable impurities.
[0008] As an optional implementation, the chemical composition of the heat-resistant aluminum alloy, by mass fraction, includes: Cu: 3.85%–4.15%, Ni: 1.4%–1.6%, Mg: 0.3%–0.4%, Si: 0.9%–1.1%, Zr: 0.025%–0.035%, Er: 0.014%–0.016%, Sr: 0.018%–0.022%, with the remainder being Al and unavoidable impurities.
[0009] As an optional implementation, the heat-resistant aluminum alloy has a density greater than 99.98%; and / or
[0010] The heat-resistant aluminum alloy has a density greater than 2.75–2.85 g / cm³. 3 .
[0011] As an optional implementation, the heat-resistant aluminum alloy exhibits the following properties at room temperature: yield strength of 300 MPa to 350 MPa, tensile strength of 450 MPa to 535 MPa, and elongation of 10% to 15%; and / or
[0012] The heat-resistant aluminum alloy exhibits the following properties at 400℃: yield strength of 150MPa~180MPa, tensile strength of 200MPa~260MPa, and elongation of 20%~25%.
[0013] Secondly, embodiments of this application provide a method for preparing a heat-resistant aluminum alloy, the method comprising:
[0014] The resulting alloy powder has the following chemical composition by mass fraction: Cu: 3.50%–4.50%, Ni: 1.00%–2.00%, Mg: 0.01%–0.75%, Si: 0.5%–1.5%, Zr: 0.01%–0.05%, Er: 0.01%–0.02%, Sr: 0.01%–0.03%, with the remainder being Al and unavoidable impurities.
[0015] The alloy powder is melted and solidified using selective laser or electron beam melting to obtain a heat-resistant aluminum alloy. The microstructure of the heat-resistant aluminum alloy includes a primary eutectic phase, a secondary eutectic phase, a Si phase, and a Mg2Si phase. The primary eutectic phase has a three-dimensional network framework structure and includes Al2Cu and Al2CuMg phases. The secondary eutectic phase, Si phase, and Mg2Si phase are distributed within the primary eutectic phase. The secondary eutectic phase includes an Al3Ni phase, and the Mg2Si phase is granular.
[0016] In the above implementation process, laser or electron beam is selected as the energy source to scan the alloy powder, achieving a metallurgical bonding effect through rapid melting and solidification. This ultimately yields a dense metal part with excellent mechanical properties, as designed in the model, with a wide process window. The solidification and forming processes are integrated into one, resulting in rapid cooling without the need for heat treatment, significantly shortening the processing cycle, improving production efficiency, and simplifying the process flow. Simultaneously, it avoids the deformation and warping problems that occur during heat treatment of complex thin-walled and variable cross-section structures, enabling complex, customized, and lightweight material processing. Furthermore, the resulting heat-resistant aluminum alloy possesses high strength, high toughness, high heat resistance, and low density, meeting the requirements of various working conditions and solving the problems of low strength and poor high-temperature stability in existing heat-resistant aluminum alloys.
[0017] As an optional embodiment, the alloy powder has an average particle size of 40–45 μm; and / or
[0018] The oxygen content of the alloy powder is less than 100 ppm; and / or
[0019] The alloy powder is spherical, and / or
[0020] The sphericity of the alloy powder is greater than 98%.
[0021] In selective laser or electron beam melting (SLM) forming of mixed powders, the powder particles are first spread into a powder layer by a powder spreading mechanism. The particle size affects the thickness of the powder layer; smaller particles result in a larger specific surface area and increased sintering driving force. SLM uses lasers or electron beams as its energy source, providing a fine spot size that easily melts fine powders. Controlling the average particle size of the alloy powder to 40–45 μm can improve the melt / sintering density and enhance print quality. Simultaneously, good powder flowability is crucial for obtaining a uniform and smooth powder layer. Generally, spherical or near-spherical powders have good flowability, are less prone to clogging the powder supply system during printing, and can be spread into thin layers. This improves the dimensional accuracy, surface quality, density, and microstructure uniformity of the alloy formed by SLM, thus enhancing overall alloy quality. Therefore, controlling the sphericity of the alloy powder to be greater than 98% can improve product quality.
[0022] As an optional implementation, the process parameters of the selective laser or electron beam melting forming method include: power of 200-500W, spot diameter of 50-90μm, scanning speed of 800-1800mm / s, scanning spacing of 70-110μm, powder thickness of 25-35μm, scanning path rotation of 30°-36° or 64°-70° per layer, and melt pool overlap rate of 15%-25%.
[0023] In the above implementation process, by controlling the parameters related to laser, scanning, powder and temperature, it is suitable for the processing of aluminum alloy powder, which can avoid the generation of large thermal stress inside the product, thereby avoiding the product from warping, cracking and other adverse phenomena, and at the same time avoiding defects such as porosity and spheroidization.
[0024] As an optional implementation, the obtained alloy powder comprises:
[0025] Aluminum ingots are heated and melted into a liquid alloy;
[0026] The alloy liquid is converted into alloy powder by gas atomization powder preparation.
[0027] The powder produced by gas atomization has better sphericity and particle size distribution that meets the requirements for use. At the same time, gas atomization powder production is less expensive than the rotating electrode method.
[0028] Thirdly, embodiments of this application provide an application of a heat-resistant aluminum alloy, wherein the heat-resistant aluminum alloy is the heat-resistant aluminum alloy described in the first aspect or a material prepared by the method for preparing the heat-resistant aluminum alloy described in the second aspect, and the application includes using the heat-resistant aluminum alloy to prepare components for high-temperature working environments, wherein the maximum temperature of the high-temperature working environment is not lower than 400°C. Attached Figure Description
[0029] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0030] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0031] Figure 1 This is a first microstructure diagram of the heat-resistant aluminum alloy provided in Embodiment 1 of this application;
[0032] Figure 2 This is a second microstructure diagram of the heat-resistant aluminum alloy provided in Embodiment 1 of this application;
[0033] Figure 3 Transmission scanning-energy dispersive spectroscopy (EDS) analysis of the heat-resistant aluminum alloy provided in Example 1 of this application;
[0034] Figure 4 A flowchart illustrating the method provided in an embodiment of this application. Detailed Implementation
[0035] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0036] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0037] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.
[0038] In this application, unless otherwise stated, directional terms such as "upper" and "lower" specifically refer to the drawing directions in the accompanying drawings. Furthermore, in the description of this application, terms such as "comprising" and "including" mean "including but not limited to." In this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this document, "and / or" describes the relationship between related objects, indicating that three relationships can exist; for example, A and / or B can represent: A alone, A and B simultaneously, or B alone. A and B can be singular or plural. In this document, "at least one" means one or more, and "more than one" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be a single or multiple.
[0039] Figure 1 and 2 Microstructure of the heat-resistant aluminum alloy provided in the embodiments of this application. Figure 3 Transmission scanning-energy dispersive spectroscopy (EDS) analysis of the heat-resistant aluminum alloy provided in the embodiments of this application is as follows: Figures 1 to 3 As shown, this application provides a heat-resistant aluminum alloy. The chemical composition of the heat-resistant aluminum alloy, by mass fraction, includes: Cu: 3.50%–4.50%, Ni: 1.00%–2.00%, Mg: 0.01%–0.75%, Si: 0.5%–1.5%, Zr: 0.01%–0.05%, Er: 0.01%–0.02%, Sr: 0.01%–0.03%, with the remainder being Al and unavoidable impurities. The microstructure of the heat-resistant aluminum alloy includes a primary eutectic phase, a secondary eutectic phase, a Si phase, and a Mg2Si phase. The primary eutectic phase has a three-dimensional network framework structure and includes Al2Cu and Al2CuMg phases. The secondary eutectic phase, Si phase, and Mg2Si phase are distributed within the primary eutectic phase. The secondary eutectic phase includes Al3Ni phase, and the Mg2Si phase is granular.
[0040] Cu can precipitate the Al2Cu phase in aluminum alloys, which plays a role in precipitation strengthening.
[0041] Ni can precipitate nickel-rich phases such as Al3Ni in aluminum alloys, which can improve the mechanical properties of aluminum alloys while also improving their heat resistance.
[0042] Si can reduce the solidification shrinkage rate and hot cracking tendency of the alloy. At the same time, due to the high cooling rate, a large amount of fine, stable, and high-hardness eutectic silicon can be precipitated and distributed in the aluminum matrix, enhancing the overall performance of the alloy.
[0043] Mg can improve the flowability of alloy powder and enhance powder quality. Simultaneously, Mg can precipitate as the Mg₂Si phase, strengthening the material. Other rare earth elements such as Y, Zr, and Er also form reinforcing phases with Al.
[0044] In some embodiments, the chemical composition of the heat-resistant aluminum alloy, by mass fraction, includes: Cu: 3.75%–4.25%, Ni: 1.25%–1.75%, Mg: 0.2%–0.5%, Si: 0.75%–1.25%, Zr: 0.02%–0.04%, Er: 0.0125%–0.0175%, Sr: 0.015%–0.025%, with the remainder being Al and unavoidable impurities.
[0045] In some embodiments, the chemical composition of the heat-resistant aluminum alloy, by mass fraction, includes: Cu: 3.85%–4.15%, Ni: 1.4%–1.6%, Mg: 0.3%–0.4%, Si: 0.9%–1.1%, Zr: 0.025%–0.035%, Er: 0.014%–0.016%, Sr: 0.018%–0.022%, with the remainder being Al and unavoidable impurities.
[0046] In some embodiments, the density of the heat-resistant aluminum alloy is greater than 99.98%; the density of the heat-resistant aluminum alloy is greater than 2.75–2.85 g / cm³. 3 The heat-resistant aluminum alloy exhibits the following properties at room temperature: yield strength of 300 MPa to 350 MPa, tensile strength of 450 MPa to 535 MPa, and elongation of 10% to 15%; and the heat-resistant aluminum alloy exhibits the following properties at 400°C: yield strength of 150 MPa to 180 MPa, tensile strength of 200 MPa to 260 MPa, and elongation of 20% to 25%.
[0047] This heat-resistant aluminum alloy, through the control of its chemical composition, forms a three-dimensional network framework microstructure with nanoscale eutectic Al2Cu and Al2CuMg phases. The uniform distribution of the Al2Cu and Al2CuMg phases in the network structure enhances the aluminum matrix. This nanoscale network framework effectively hinders dislocation movement and microcrack propagation, breaking the scale effect of traditional solidification structures and resulting in significant strengthening. The Al3Ni phase, a secondary eutectic phase, exhibits good high-temperature stability, remaining stable even at 400℃, and can coat and suppress aluminum matrix deformation. The Si phase, a tertiary eutectic phase, is fine and stable, distributed within the matrix, effectively increasing the material's hardness, tensile strength, wear resistance, and corrosion resistance. These three phases mutually nucleate and form a fine mixed eutectic structure, providing casting performance and plasticity; simultaneously, the granular Mg2Si phase within the structure provides strengthening. This gives the heat-resistant aluminum alloy the characteristics of high strength, high toughness, high heat resistance and low density, which can meet the requirements of different working conditions and solve the problems of low strength and poor high temperature stability of existing heat-resistant aluminum alloys.
[0048] Based on the same inventive concept Figure 4 A flowchart of the method provided in the embodiments of this application is shown below. Figure 4 As shown in the embodiments of this application, a method for preparing a heat-resistant aluminum alloy is also provided, the method comprising:
[0049] S1. Obtain alloy powder, the chemical composition of which, by mass fraction, comprises: Cu: 3.50%–4.50%, Ni: 1.00%–2.00%, Mg: 0.01%–0.75%, Si: 0.5%–1.5%, Zr: 0.01%–0.05%, Er: 0.01%–0.02%, Sr: 0.01%–0.03%, with the remainder being Al and unavoidable impurities.
[0050] In some embodiments, obtaining the alloy powder includes:
[0051] S1.1. Heat and melt aluminum ingots into a liquid alloy;
[0052] Specifically, in this embodiment, under a protective atmosphere, aluminum ingots are heated and melted into molten aluminum; desired elements are added to the molten aluminum to form an alloy liquid, such that the alloy liquid contains the following preset composition by mass percentage: Cu 3.50%–4.50%, Ni 1.00%–2.00%, Mg 0.01%–0.75%, Si 0.5%–1.5%, Zr 0.01%–0.05%, Er 0.01%–0.02%, Sr 0.01%–0.03%, with the remainder being Al and unavoidable impurities.
[0053] S1.2. The alloy liquid is made into alloy powder by gas atomization powder making.
[0054] Specifically, in this embodiment, the molten alloy is discharged through a guide tube, and a high-pressure airflow is used to impact the molten alloy at the outlet of the guide tube, causing the molten alloy to form fine droplets; during the condensation process, the droplets eventually form spherical alloy powder under the action of surface tension.
[0055] In some embodiments, the average particle size of the alloy powder is 40-45 μm; the oxygen content of the alloy powder is less than 100 ppm; in the melting and solidification forming of mixed powder using selective laser or electron beam melting, the powder particles are first spread into a powder layer under the action of the powder spreading mechanism. The size of the powder particle size affects the thickness of the powder spreading layer. The smaller the powder particle size, the larger the specific surface area and the increased sintering driving force. The energy source of selective laser or electron beam melting is a laser or electron beam, which has a fine spot and is easier to melt fine powder. Controlling the average particle size of the alloy powder to 40-45 μm can improve the melt / sintering density and improve the printing quality.
[0056] In some embodiments, the alloy powder is spherical, preferably with a sphericity greater than 98%. Good powder flowability is crucial for obtaining a uniform and smooth powder layer. Generally, spherical or near-spherical powders have good flowability, are less likely to clog the powder supply system during printing, and can be spread into thin layers. This improves the dimensional accuracy, surface quality, density, and microstructure uniformity of alloys formed by selective laser or electron beam melting, thereby improving the overall quality of the alloy. Therefore, controlling the sphericity of the alloy powder to be greater than 98% can improve product quality.
[0057] S2. The alloy powder is melted and solidified using selective laser or electron beam melting to obtain a heat-resistant aluminum alloy. The microstructure of the heat-resistant aluminum alloy includes a primary eutectic phase, a secondary eutectic phase, a Si phase, and a Mg2Si phase. The primary eutectic phase has a three-dimensional network framework structure and includes Al2Cu and Al2CuMg phases. The secondary eutectic phase, Si phase, and Mg2Si phase are distributed within the primary eutectic phase. The secondary eutectic phase includes an Al3Ni phase, and the Mg2Si phase is granular.
[0058] In some embodiments, the process parameters of the selective laser or electron beam melting forming method include: power of 200–500 W, spot diameter of 50–90 μm, scanning speed of 800–1800 mm / s, scanning spacing of 70–110 μm, powder thickness of 25–35 μm, scanning path rotation of 30°–36° or 64°–70° per layer, and melt pool overlap rate of 15%–25%. By controlling the parameters related to laser, scanning, powder, and temperature, it is suitable for processing alloy powders, avoiding large thermal stresses inside the product, thereby preventing defects such as warping and cracking, and also avoiding defects such as porosity and spheroidization.
[0059] In this method, when using selective laser or electron beam melting to melt and solidify mixed powders, the powder particles are first spread into a powder layer under the action of a powder spreading mechanism. The size of the powder particles affects the thickness of the powder layer; the smaller the powder particle size, the larger the specific surface area, and the greater the sintering driving force. Selective laser or electron beam melting uses a laser or electron beam as its energy source, with a fine spot size that easily melts fine powders. Controlling the average particle size of the alloy powder to 40–45 μm can improve the melt / sintering density and enhance print quality. Simultaneously, good powder flowability is crucial for obtaining a uniform and smooth powder layer. Generally, spherical or near-spherical powders have good flowability, are less likely to clog the powder supply system during printing, and can be spread into a thin layer. This improves the dimensional accuracy, surface quality, density, and microstructure uniformity of the alloy melted and formed by selective laser or electron beam melting, thus improving the overall quality of the alloy. Therefore, controlling the sphericity of the alloy powder to be greater than 98% can improve product quality.
[0060] Based on the same inventive concept, this application also provides an application of a heat-resistant aluminum alloy, wherein the heat-resistant aluminum alloy is the heat-resistant aluminum alloy provided above or a material prepared by the heat-resistant aluminum alloy preparation method provided above, and the application includes using the heat-resistant aluminum alloy to prepare components for high-temperature working environments, wherein the maximum temperature of the high-temperature working environment is not lower than 400°C.
[0061] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. If there is no corresponding national standard, then general international standards, conventional conditions, or conditions recommended by the manufacturer are followed.
[0062] Comparative Example 1
[0063] This embodiment provides a method for preparing a heat-resistant aluminum alloy, which is carried out according to the following steps:
[0064] S1. Under the protection of high-purity argon gas, aluminum ingots are heated and melted into molten aluminum in an induction furnace. The required alloying elements are added to the molten aluminum, adjusting the proportions of each element to: Cu 4.00 wt%, Ni 0.5 wt%, Mg 0.01 wt%, Si 0.5 wt%, Zr 0.01 wt%, Er 0.01 wt%, Sr 0.02 wt%, with the remainder being aluminum. The mixture is then degassed and slag removed to achieve the predetermined composition, forming an alloy liquid.
[0065] S2, the alloy liquid is discharged through a guide tube, and high-pressure argon gas is used to impact the alloy liquid at the outlet of the guide tube to form fine droplets; during the condensation process, the droplets eventually form spherical alloy powder under the action of surface tension. The aluminum alloy powder has an average particle size of 43.5 μm, an oxygen content of less than 100 ppm, and a sphericity of greater than 98%.
[0066] S3 utilizes selective laser melting (SLM) forming with the following process parameters: laser power 330W, spot diameter 70μm, scanning speed 1200mm / s, scanning spacing 90μm, layer thickness 30μm, scanning path rotation of 67° per layer, and melt pool overlap rate of 20%. This rapidly melts and solidifies spherical alloy powder to obtain a high-strength, high-toughness, and heat-resistant Al-Cu-Ni-Mg-Si aluminum alloy material.
[0067] like Figure 1 As shown in the figure, the high-strength, high-toughness, and heat-resistant Al-Cu-Ni-Mg-Si aluminum alloy material has a nanoscale eutectic three-dimensional network framework structure.
[0068] Tests showed a density greater than 99.98%, with a density of 2.797 g / cm³. 3 Its room temperature yield strength is 335 MPa, tensile strength is 478 MPa, and elongation is 11%. Above 400℃, the yield strength is 150 MPa, tensile strength is 220 MPa, and elongation is 21%.
[0069] Example 1
[0070] This embodiment provides a method for preparing a heat-resistant aluminum alloy, which is carried out according to the following steps:
[0071] S1. Under the protection of high-purity argon gas, aluminum ingots are heated and melted into molten aluminum in an induction furnace. The required alloying elements are added to the molten aluminum, adjusting the proportions of each element to: Cu 3.9 wt%, Ni 2.00 wt%, Mg 0.2 wt%, Si 0.6 wt%, Zr 0.01 wt%, Er 0.01 wt%, Sr 0.02 wt%, with the remainder being aluminum. The mixture is then degassed and slag removed to achieve the predetermined composition, forming an alloy liquid.
[0072] S2, the alloy liquid is discharged through a guide tube, and high-pressure argon gas is used to impact the alloy liquid at the outlet of the guide tube to form fine droplets; during the condensation process, the droplets eventually form spherical alloy powder under the action of surface tension. The aluminum alloy powder has an average particle size of 45μm, an oxygen content of less than 100ppm, and a sphericity of greater than 98%.
[0073] S3 utilizes selective laser melting (SLM) forming with the following process parameters: laser power of 500W, spot diameter of 70μm, scanning speed of 1800mm / s, scanning spacing of 90μm, layer thickness of 30μm, scanning path rotation of 33° per layer, and melt pool overlap rate of 20%. This rapidly melts and solidifies spherical alloy powder to obtain a high-strength, high-toughness, and heat-resistant Al-Cu-Ni-Mg-Si aluminum alloy material.
[0074] Testing revealed that its tissue possesses a nanoscale eutectic three-dimensional network framework structure; its density is greater than 99.98%, with a density of 2.83 g / cm³. 3 Its room temperature yield strength is 332 MPa, tensile strength is 470 MPa, and elongation is 10%. Above 400℃, the yield strength is 170 MPa, tensile strength is 245 MPa, and elongation is 20%.
[0075] Example 2
[0076] This embodiment provides a method for preparing a heat-resistant aluminum alloy, which is carried out according to the following steps:
[0077] S1, under the protection of high-purity argon gas, aluminum ingots are heated and melted into molten aluminum in an induction furnace. The required alloying elements are added to the molten aluminum, and the proportions of each element are adjusted as follows: Cu 4.50 wt%, Ni 1.00 wt%, Mg 0.3 wt%, Si 0.5 wt%, Zr 0.03 wt%, Er 0.02 wt%, Sr 0.03 wt%, with the remainder being aluminum. The mixture is degassed and slag removed to achieve the preset composition, forming an alloy liquid.
[0078] S2, the alloy liquid is discharged through a guide tube, and high-pressure argon gas is used to impact the alloy liquid at the outlet of the guide tube to form fine droplets; during the condensation process, the droplets eventually form spherical alloy powder under the action of surface tension. The aluminum alloy powder has an average particle size of 40.4 μm, an oxygen content of less than 100 ppm, and a sphericity of greater than 98%.
[0079] S3 utilizes selective laser melting (SLM) forming with the following process parameters: laser power 750W, spot diameter 70μm, scanning speed 1800mm / s, scanning spacing 90μm, layer thickness 30μm, scanning path rotation of 33° per layer, and melt pool overlap rate of 20%. This rapidly melts and solidifies spherical alloy powder to obtain a high-strength, high-toughness, and heat-resistant Al-Cu-Ni-Mg-Si aluminum alloy material.
[0080] Testing revealed that its tissue possesses a nanoscale eutectic three-dimensional network framework structure; its density is greater than 99.98%, with a density of 2.81 g / cm³. 3 Its room temperature yield strength is 330 MPa, tensile strength is 500 MPa, and elongation is 13.5%. Above 400℃, the yield strength is 165 MPa, tensile strength is 220 MPa, and elongation is 25%.
[0081] Example 3
[0082] This embodiment provides a method for preparing a heat-resistant aluminum alloy, which is carried out according to the following steps:
[0083] S1. Under the protection of high-purity argon gas, aluminum ingots are heated and melted into molten aluminum in an induction furnace. The required alloying elements are added to the molten aluminum, and the proportions of each element are adjusted as follows: Cu 4.00 wt%, Ni 1.0 wt%, Mg 0.01 wt%, Si 0.5 wt%, Zr 0.01 wt%, Er 0.01 wt%, Sr 0.02 wt%, with the remainder being aluminum. The mixture is degassed and slag removed to achieve the preset composition, forming an alloy liquid.
[0084] S2, the alloy liquid is discharged through a guide tube, and high-pressure argon gas is used to impact the alloy liquid at the outlet of the guide tube to form fine droplets; during the condensation process, the droplets eventually form spherical alloy powder under the action of surface tension. The aluminum alloy powder has an average particle size of 40.4 μm, an oxygen content of less than 100 ppm, and a sphericity of greater than 98%.
[0085] S3 utilizes selective laser melting (SLM) forming with the following process parameters: laser power of 600W, spot diameter of 70μm, scanning speed of 1500mm / s, scanning spacing of 90μm, layer thickness of 30μm, scanning path rotation of 67° per layer, and melt pool overlap rate of 20%. This rapidly melts and solidifies spherical alloy powder to obtain a high-strength, high-toughness, and heat-resistant Al-Cu-Ni-Mg-Si aluminum alloy material.
[0086] Testing revealed that its tissue possesses a nanoscale eutectic three-dimensional network framework structure with a density greater than 99.98% and a density of 2.78 g / cm³. 3 Its room temperature yield strength is 350 MPa, tensile strength is 535 MPa, and elongation is 15%. Above 400℃, the yield strength is 175 MPa, tensile strength is 240 MPa, and elongation is 25%.
[0087] Example 4
[0088] This embodiment provides a method for preparing a heat-resistant aluminum alloy, which is carried out according to the following steps:
[0089] S1. Under the protection of high-purity argon gas, aluminum ingots are heated and melted into molten aluminum in an induction furnace. The required alloying elements are added to the molten aluminum, and the proportions of each element are adjusted as follows: Cu 4.50 wt%, Ni 2.00 wt%, Mg 0.75 wt%, Si 1.5 wt%, Zr 0.05 wt%, Er 0.02 wt%, Sr 0.01 wt%, with the remainder being aluminum. The mixture is degassed and slag removed to achieve the preset composition, forming an alloy liquid.
[0090] S2, the alloy liquid is discharged through a guide tube, and high-pressure argon gas is used to impact the alloy liquid at the outlet of the guide tube to form fine droplets; during the condensation process, the droplets eventually form spherical alloy powder under the action of surface tension. The aluminum alloy powder has an average particle size of 43μm, an oxygen content of less than 100ppm, and a sphericity of greater than 98%.
[0091] S3 utilizes selective laser melting (SLM) forming with the following process parameters: laser power 300W, spot diameter 70μm, scanning speed 1000mm / s, scanning spacing 90μm, layer thickness 30μm, scanning path rotation of 67° per layer, and melt pool overlap rate of 20%. This rapidly melts and solidifies spherical alloy powder to obtain a high-strength, high-toughness, and heat-resistant Al-Cu-Ni-Mg-Si aluminum alloy material.
[0092] Testing revealed that its tissue possesses a nanoscale eutectic three-dimensional network framework structure with a density greater than 99.98% and a density of 2.796 g / cm³. 3 Its room temperature yield strength is 325 MPa, tensile strength is 525 MPa, and elongation is 12%. Above 400℃, the yield strength is 180 MPa, tensile strength is 235 MPa, and elongation is 22%.
[0093] Example 5
[0094] This embodiment provides a method for preparing a heat-resistant aluminum alloy, which is carried out according to the following steps:
[0095] S1. Under the protection of high-purity argon gas, aluminum ingots are heated and melted into molten aluminum in an induction furnace. The required alloying elements are added to the molten aluminum, and the proportions of each element are adjusted as follows: Cu 3.50 wt%, Ni 1.50 wt%, Mg 0.5 wt%, Si 0.8 wt%, Zr 0.01 wt%, Er 0.01 wt%, Sr 0.01 wt%, with the remainder being aluminum. The mixture is degassed and slag removed to achieve the preset composition, forming an alloy liquid.
[0096] S2, the alloy liquid is discharged through a guide tube, and high-pressure argon gas is used to impact the alloy liquid at the outlet of the guide tube to form fine droplets; during the condensation process, the droplets eventually form spherical alloy powder under the action of surface tension. The aluminum alloy powder has an average particle size of 45μm, an oxygen content of less than 100ppm, and a sphericity of greater than 98%.
[0097] S3 utilizes selective laser melting (SLM) forming with the following process parameters: laser power of 200W, spot diameter of 70μm, scanning speed of 800mm / s, scanning spacing of 90μm, layer thickness of 30μm, scanning path rotation of 33° per layer, and melt pool overlap rate of 20%. This rapidly melts and solidifies spherical alloy powder to obtain a high-strength, high-toughness, and heat-resistant Al-Cu-Ni-Mg-Si aluminum alloy material.
[0098] Testing revealed that its tissue possesses a nanoscale eutectic three-dimensional network framework structure with a density greater than 99.9% and a density of 2.842 g / cm³. 3Its room temperature yield strength is 325 MPa, tensile strength is 460 MPa, and elongation is 12%. Above 400℃, the yield strength is 170 MPa, tensile strength is 260 MPa, and elongation is 22%.
[0099] The performance of the heat-resistant aluminum alloys provided in Examples 1 to 6 was tested, and the results are shown in the table below:
[0100]
[0101] As can be seen from the table above, the heat-resistant aluminum alloy obtained by the method provided in the embodiments of this application has the characteristics of high strength, high toughness, high heat resistance and low density, which can meet the usage requirements of different working conditions.
[0102] The above description is merely a specific embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A heat-resistant aluminum alloy, characterized in that, The chemical composition of the heat-resistant aluminum alloy is expressed as a mass fraction. The composition includes: Cu: 3.50%~4.50%, Ni: 1.00%~2.00%, Mg: 0.01%~0.75%, Si: 0.5%~1.5%, Zr: 0.01%~0.05%, Er: 0.01%~0.02%, Sr: 0.01%~0.03%, with the remainder being Al and unavoidable impurities. The microstructure of the heat-resistant aluminum alloy includes a primary eutectic phase, a secondary eutectic phase, a Si phase, and a Mg2Si phase. The primary eutectic phase has a three-dimensional network framework structure and includes Al2Cu and Al2CuMg phases. The secondary eutectic phase, Si phase, and Mg2Si phase are distributed within the primary eutectic phase. The secondary eutectic phase includes Al3Ni phase, and the Mg2Si phase is granular.
2. The heat-resistant aluminum alloy according to claim 1, characterized in that, The chemical composition of the heat-resistant aluminum alloy is expressed as a mass fraction. It includes: Cu: 3.75%~4.25%, Ni: 1.25%~1.75%, Mg: 0.2%~0.5%, Si: 0.75%~1.25%, Zr: 0.02%~0.04%, Er: 0.0125%~0.0175%, Sr: 0.015%~0.025%, with the remainder being Al and unavoidable impurities.
3. The heat-resistant aluminum alloy according to claim 1, characterized in that, The chemical composition of the heat-resistant aluminum alloy is expressed as a mass fraction. It includes: Cu: 3.85%~4.15%, Ni: 1.4%~1.6%, Mg: 0.3%~0.4%, Si: 0.9%~1.1%, Zr: 0.025%~0.035%, Er: 0.014%~0.016%, Sr: 0.018%~0.022%, with the remainder being Al and unavoidable impurities.
4. The heat-resistant aluminum alloy according to any one of claims 1 to 3, characterized in that, The heat-resistant aluminum alloy has a density greater than 99.98%; and / or The density of the heat-resistant aluminum alloy is 2.75~2.85 g / cm³. 3 .
5. The heat-resistant aluminum alloy according to any one of claims 1 to 3, characterized in that, The heat-resistant aluminum alloy exhibits the following properties at room temperature: yield strength of 300 MPa to 350 MPa, tensile strength of 450 MPa to 535 MPa, and elongation of 10% to 15%; and / or The heat-resistant aluminum alloy exhibits the following properties at 400℃: yield strength of 150MPa~180MPa, tensile strength of 200MPa~260MPa, and elongation of 20%~25%.
6. A method for preparing a heat-resistant aluminum alloy, characterized in that, The method includes: The resulting alloy powder has the following chemical composition by mass fraction: Cu: 3.50%~4.50%, Ni: 1.00%~2.00%, Mg: 0.01%~0.75%, Si: 0.5%~1.5%, Zr: 0.01%~0.05%, Er: 0.01%~0.02%, Sr: 0.01%~0.03%, with the remainder being Al and unavoidable impurities; The alloy powder is melted and solidified using selective laser or electron beam melting to obtain a heat-resistant aluminum alloy. The microstructure of the heat-resistant aluminum alloy includes a primary eutectic phase, a secondary eutectic phase, a Si phase, and a Mg2Si phase. The primary eutectic phase has a three-dimensional network framework structure and includes Al2Cu and Al2CuMg phases. The secondary eutectic phase, Si phase, and Mg2Si phase are distributed within the primary eutectic phase. The secondary eutectic phase includes an Al3Ni phase, and the Mg2Si phase is granular.
7. The method for preparing the heat-resistant aluminum alloy according to claim 6, characterized in that, The alloy powder has an average particle size of 40~45μm; and / or The oxygen content of the alloy powder is less than 100 ppm; and / or The sphericity of the alloy powder is greater than 98%.
8. The method for preparing the heat-resistant aluminum alloy according to claim 6, characterized in that, The process parameters of the selected area laser or electron beam melting forming method include: power of 200~500W, spot diameter of 50~90μm, scanning speed of 800~1800mm / s, scanning spacing of 70~110μm, powder thickness of 25~35μm, scanning path rotation of 30°~36° or 64°~70° per layer, and melt pool overlap rate of 15%~25%.
9. The method for preparing the heat-resistant aluminum alloy according to claim 6, characterized in that, The obtained alloy powder includes: Aluminum ingots are heated and melted into a liquid alloy; The alloy liquid is converted into alloy powder by gas atomization powder preparation.
10. An application of a heat-resistant aluminum alloy, characterized in that, The heat-resistant aluminum alloy is any one of the heat-resistant aluminum alloys according to claims 1 to 5 or a material prepared by the method of any one of the heat-resistant aluminum alloys according to claims 6 to 9. The application includes using the heat-resistant aluminum alloy to prepare components for high-temperature working environments, wherein the high-temperature working environment is not lower than 400°C.
Citation Information
Patent Citations
Aluminum alloy and aluminum alloy structural member
CN112779443A
Laser additive manufacturing high-strength heat-resistant rare earth aluminum alloy and preparation method thereof
CN112795818A
Heat-resistant and wear-resistant aluminum alloy
JP1991294446A